Some practical and biological information useful for Zoraptera (Insecta) studies - Rafael, José A.; Xavier Filho, Francisco F.; Vidal, João F. (Entomological Communications, 2025)
The data presented here summarizes essential information to enhance the collections and breeding of Zoraptera. We present our experience collecting specimens, primarily in the Amazon Basin, ranging from the precarious use of soft paintbrushes to the highly effective method of using a lightweight 9-volt portable aspirator when exploring under the bark of rotting wood and on the sheaths of live plants. The portable aspirator transformed the Instituto Nacional de Pesquisas da Amazônia (INPA) Zoraptera collection into the largest in the world, with over 4,500 specimens. We use a headlamp better to see the dark adult specimens against the dark substrate. We report on a mixed colony comprising more than 1,000 specimens on the same fallen trunk. We provide an easy method for growing specimens in the laboratory to obtain eggs, nymphs, and adults. We also present a rapid identification method for live specimens manipulated over a small amount of water using a soft paintbrush. Based on more than 3,000 specimens collected for Brazilozoros huxleyi Bolivar y Pieltain & Coronado, 1963 and Brazilozoros weidneri New, 1978 we obtained only 2% of the alated specimens in the field. The sex ratio for both species was close to 1:1.